Peningkatan Kemampuan Memahami Pengamalan Hukum Ibadah dari Al-Qur'an Melalui Program Pendampingan Santri di Pondok Pesantren Qur’any Jombang - Qurrotul Ainiyah; Mihmidaty Ya’cub; Julianne Kamelia Riza; Dita Dzata Mirrota; Khumairoh An Nahdliyah (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
This mentoring program aims to analyze the improvement of students’ ability in comprehending the legal verses of the Qur’an after participating in a mentoring program organized at the Qurany Islamic Boarding School. The mentoring was carried out for 3 months by implementing interactive lectures, group discussions, case studies and hands-on practice. The results demonstrated that the abilities in fluent recitation, translation, analyzing verse structures, grasping content, and application in daily worship increased significantly with the percentage of excellent grades reaching >90%. This success was influenced by the utilization of appropriate training methods, resource competencies, participant enthusiasm, and support from the Islamic boarding school. Through this successful mentoring, the students’ theoretical understanding and practical skills with regards to the application of the Qur’anic legal verses have become very adequate, enabling them to become pioneers in society.